Cellulose extraction by biomass valorization of prickly pear seed waste - Ben Ali, Nesrine; Abdedayem, Asma; Nouri, Hanen; Ben-Ali, Samia (Comptes Rendus. Chimie)
The main objective of this work was the valorization of various biowastes to extract biocellulose for carbon fiber synthesis as a subsequent application. The effectiveness of cellulose extraction was investigated by two methods: maceration extraction and Soxhlet process. The extracted cellulose was characterized using a range of analytical techniques: thermogravimetric analysis/differential thermal analysis, scanning electron microscopy, Fourier transform infrared spectroscopy (FTIR), and energy-dispersive X-ray (EDX) analysis. The purity of extracted cellulose was successfully confirmed by FTIR and EDX results, which indicated the presence of major functional groups characteristic of cellulose structure. The cellulose extraction yield from prickly pear seeds was 39.3% by maceration and 23.18% using the Soxhlet extraction method.